Return loss improvement of radial line slot array antennas on closed ring resonator structure at 28 GHz - Kamaruddin, Rabiatul Adawiyah Azian; Mohd Ibrahim, Imran; Al-Gburi, Ahmed Jamal Abdullah; Zakaria, Zahriladha; Shairi, Noor Azwan; Abdul Rahman, Tharek; Purnamirza, Teddy (Wydawnictwo SIGMA-NOT, 2021)
This paper aims to investigate and design a radial line slot array antenna (RSLA) with closed ring resonator (CRR) for return loss improvement. The CRR printed on a dielectric substrate with a circumference alignment position attached to the RLSA antenna. The CRR structure used the combination of the four rings with a rectangular shape and showed a response in the range of 25.30 GHz up to 31.40 GHz. It is worth mentioning that applying a gap cavity height (h) of the superstrate layer to the CRR structure is needed to improve the return loss significantly. However, as the superstrate layer of the CRR structure is increased the value of the gap cavity height must be adjustable to ensure that the return loss is maintained at the same resonant frequency. The return loss performance showed a significant improvement from -10.30 dB to -12.34 dB for λ/4 gap between the antenna and the superstrate